Melampaui Cedera Fisik: Kehamilan pada Anak sebagai Bentuk Kerusakan Reproduksi dalam Kejahatan Seksual terhadap Anak - Frilia Shafitri Hardi; Nurini Aprilianda; Faizin Sulistio (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2026)
Pregnancy in children who are victims of sexual assault is a serious disruption to reproductive function because the child's body is not yet biologically and physiologically mature enough to undergo the process of pregnancy. The immaturity of the reproductive organs, including the endocrine system, pelvis, and uterus, puts the child at high risk of medical complications such as pre-eclampsia, hemorrhage, obstructed labor, obstetric fistula, and even the potential for long-term infertility. From a victimological viewpoint, pregnancy is not merely a direct result of sexual violence; it also prolongs victimization due to the loss of bodily autonomy, various psychological traumas, and the risk of secondary victimization stemming from social stigma. This research investigates child pregnancy as a sign of reproductive dysfunction or disorder as defined in Article 81, Paragraph (5) of the Child Protection Law. The study employs a normative-legal approach, analyzing legal texts, court decisions, and academic literature. The findings indicate that child pregnancy is a form of reproductive disorder, which is legally classified as a disturbance or reduction in reproductive capacity, thus providing grounds for harsher penalties. A rethinking of legal understanding is essential to recognize child pregnancy not just as a biological consequence, but as a reproductive loss that jeopardizes the safety, dignity, and future of the child, in line with the child’s best interests.